2013
DOI: 10.1016/j.cag.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations on Marching Cubes 33 topological correctness

Abstract: Chernyaev's Marching Cubes 33 is one of the first algorithms intended to preserve the topology of the trilinear interpolant. In this work, we address three issues with the Marching Cubes 33 algorithm, two of which are related to its original description and one that is related to its variant. In particular, we solve a problem with the core disambiguation procedure of Marching Cubes 33 that prevents the extraction of topologically correct isosurfaces for the ambiguous configuration 13.5. This work closes an exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…Manifoldness: Etiene et al [ENS*12] and Custodio et al [CEPS13] showed that manifoldness might be lost, if the topological correct triangulation of a cell introduces non‐manifold edges at cell boundary. Nelson [Nie03] presented a set of lookup tables with triangulation schemes including interior vertices generating topologically correct and consistent surfaces.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Manifoldness: Etiene et al [ENS*12] and Custodio et al [CEPS13] showed that manifoldness might be lost, if the topological correct triangulation of a cell introduces non‐manifold edges at cell boundary. Nelson [Nie03] presented a set of lookup tables with triangulation schemes including interior vertices generating topologically correct and consistent surfaces.…”
Section: Related Workmentioning
confidence: 99%
“…Whereas manifoldness can be solved by a carefully triangulation of the cell satisfying the conditions imposed by the asymptotic decider [NH91], guaranteeing topological correctness is a much more difficult problem. After the Chernyaev's MC33 appeared much effort has been spent in the development of new lookup tables and deciders to tackle topological correctness, [CGMS00, Nie03, CEPS13, LB03].…”
Section: Introductionmentioning
confidence: 99%
“…This step limits the image analysis within the lung regions and meanwhile improves the efficiency in memory and time. Second, the marching cubes algorithm (MCA) [36][37][38] is used to model the 3D lung anatomical structures as a triangle mesh surface, where airways, vessels, and other diseased or noisy regions (e.g., emphysema) are modeled [Figs. 2(c) and 2(d)].…”
Section: A Scheme Overviewmentioning
confidence: 99%
“…Na Figura (1) apresentamos malhas extraídas do dado Bonsai, referentes aos isovalores 130, 70 e 30, utilizando a versão de Custodio et al [2] do algortimo Marching Cubes.…”
Section: Introductionunclassified